2019
DOI: 10.3390/ijms20215361
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Vaginal Exposures to the Common Cosmetic and Household Preservative Methylisothiazolinone Induce Persistent, Mast Cell-Dependent Genital Pain in ND4 Mice

Abstract: A history of allergies doubles the risk of vulvodynia—a chronic pain condition of unknown etiology often accompanied by increases in numbers of vulvar mast cells. We previously established the biological plausibility of this relationship in mouse models where repeated exposures to the allergens oxazolone or dinitrofluorobenzene on the labiar skin or inside the vaginal canal of ND4 Swiss Webster outbred mice led to persistent tactile sensitivity and local increases in mast cells. In these models, depletion of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 64 publications
(111 reference statements)
1
21
0
Order By: Relevance
“…Many of these products contain the biocide preservative MI. We previously reported that vaginal exposure to MI provokes short-term provoked genital pain in ND4 mice lasting up to 21 days after 10 intravaginal exposures to 0.5% MI in sensitized mice [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these products contain the biocide preservative MI. We previously reported that vaginal exposure to MI provokes short-term provoked genital pain in ND4 mice lasting up to 21 days after 10 intravaginal exposures to 0.5% MI in sensitized mice [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here we investigated the inflammatory and nociceptive effects of dermal applications of MI which are a much more likely route of pervasive exposures to this toxic chemical that are linked to rising allergic sensitivity [ 3 ] and tissue injury [ 4 9 ]. We found that 10 dermal exposures to 0.5% MI induced pain responses that lasted much longer–up to 70 days after the last challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed a murine model of allergy-driven genital pain that recapitulates clinical characteristics of the chronic pain condition localized provoked vulvodynia, including mast cell accumulation in vaginal tissue and long-lasting tactile sensitivity to stimulation of the anogenital ridge, using repeated exposures to the allergenic cosmetic preservative methylisothiazolinone (MI) [8 , [11] , [12] . Primary fibroblast cell lines derived from vulvar biopsies of vulvodynia patients have been shown to exhibit a heightened cytokine response when treated with yeast and bacterial antigens [5 , 6] .…”
Section: Methods Validationmentioning
confidence: 99%
“…Here, we describe a novel method for the establishment of murine vaginal fibroblast cell lines, which provide a cell type-specific in vitro experimental system for investigating fibroblast behavior in pre-clinical rodent models of disease. We validate this methodology in two ways: 1) we evaluate surface marker expression and visually examine morphology of cells and 2) we demonstrate that primary fibroblasts derived from vaginal canals of previously sensitized ND4 mice repeatedly exposed to an allergic irritant in our model of chronic allergy-provoked genital pain replicate the heightened cytokine response to bacterial and yeast antigens observed in fibroblast cell lines derived from vulvar biopsies taken from vulvodynia patients [5] , [6] , 8] .…”
Section: Rationalementioning
confidence: 95%